1999
DOI: 10.1007/s007840050104
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and silver in saliva from subjects with symptoms self-related to amalgam fillings

Abstract: The amount of mercury released into saliva from dental amalgam fillings is currently being debated. Mercury enters saliva as vapor, ions and particles of amalgam. The aim of the present study was to determine mercury and silver concentrations in saliva of persons with amalgam fillings. Moreover, it was the aim to investigate whether amalgam particles were present in samples of stimulated saliva in control subjects. In that case, we also wanted to determine the influence of these particles on the mercury concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
0
12
1
1
Order By: Relevance
“…Saliva has been used to assess mercury release from amalgam fillings for adults with complaints self -related to amalgam ( Lygre et al, 1999 ). The median of mercury concentration in saliva was 9.5 g /l and therewith far beyond the findings of the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…Saliva has been used to assess mercury release from amalgam fillings for adults with complaints self -related to amalgam ( Lygre et al, 1999 ). The median of mercury concentration in saliva was 9.5 g /l and therewith far beyond the findings of the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…The slow release of Hg from amalgams is known to select for Hg-resistant bacteria in the gut [59]. Ag is also released [42] and Ag-resistant oral bacteria were recently reported [14]. Furthermore, it appears that Ag release from Wlm processing, mining sites, and dental amalgams are large sources of Ag in human wastewaters where selection for Ag resistance might also occur (e.g.…”
Section: History Of Biocidal Uses Of Silver Products In Clinical Applmentioning
confidence: 96%
“…Others have shown that a considerable part of the Hg in saliva is present as amalgam particles [18], and that Hg levels in saliva do not correlate with concentrations in blood and urine [19].…”
Section: Mercury In Saliva Obtained During ''Chewing'' Of Smokeless Tmentioning
confidence: 99%
“…Because Hg in saliva can vary depending on the presence of dental amalgams containing the element [18], two individuals were tested: one with dental amalgams and one without. Mercury concentrations for the saliva controls (before chewing) were 30.6 AE 2.3 ng mL À1 and 1.5 AE 0.5 ng mL À1 for the individual with and without dental amalgams, respectively.…”
Section: Mercury In Saliva Obtained During ''Chewing'' Of Smokeless Tmentioning
confidence: 99%